Framing Emotions on Mainstream Media Instagram Feeds During the First Wave of the COVID-19 Pandemic - Szulich-Kałuża, Justyna; Szegda, Joanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
The main goal of this paper is to answer the following questions. 1) What visual narratives about emotions are constructed and imposed by mainstream media on their Instagram channels during the COVID-19 pandemic? 2) How do they frame them by complementing existing or creating new iconic-symbolic representations of the semantic framework of selected emotions (joy, fear, sadness, anger)? The selected visual material included photos and drawings and was examined using quantitative and qualitative content analysis and comparative semiological analysis. The analysis showed a low saturation of media messages with emotions and made it possible to describe the semantic media framework of individual emotions according to the following scheme: bodily sensations, expressive gestures, social situation and emotional culture.